Mekanisme Akad Bisnis Tanah Pemakaman Alkah Mahabbah Gunung Ronggeng Martapura Kalimantan Selatan Dalam Perspektif Madzhab Imam Syafi’i - Hafidzi, Anwar; Syukran, Muhammad; Ainorridho’e, Muhammad (Program Studi Hukum Ekonomi Syariah, Institut Agama Islam Negeri Parepare, 2023)
ABSTRACT The increasing development of property assets, especially the level of difficulty selling land quickly and in cash is not as easy as we imagine with the business of buying and selling 2x1 graves of alkah land in the Banjar community, this business is used as a livelihood to take as much profit as possible among people who can't afford it . This research is a field research using a descriptive qualitative approach, namely field research with a library research approach, library research and textual comparison of a contract. The object of this research is the perspective of the Imam Syafi'I madhhab in the mechanism of the business contract of buying and selling land alkah with the funeral gift system. Data collection techniques are observation, interview, documentation and literature study. The results of this study indicate that the business mechanism of buying and selling alkah land at the Mahabbah Cemetery according to Imam Syafi'I has been allowed with the fulfillment of the conditions and pillars. According to the MUI fatwa, the funeral business is allowed but in running the business there is no tabzir and israf element because it uses something appropriate but not excessive than appropriate. Keywords: Business, Burial Ground, Alkah, Gift